Thermal performance analysis of GaN nanowire and fin-shaped power transistors based on self-consistent electrothermal simulations - Kamrani, Hamed; Yu, Feng; Frank, Kristian; Strempel, Klaas; Fatahilah, Muhammad Fahlesa; Wasisto, Hutomo Suryo; Roemer, Friedhard; Waag, Andreas; Witzigmann, Bernd (Microelectronics Reliability, 2018)
We present self-consistent electrothermal simulations of the GaN nanowire-based field-effect transistor (NWFET) and vertical fin field-effect transistor (FinFET) by taking into account all major heat flux paths. Simulation results of a NWFET validated by experimental data are compared to the results of a vertical FinFET designed with same sizes that ensures a fair comparison of their thermal performance. It is found that the peak temperature in the NWFET is close to the uppermost contact, which facilitates heat removal from top. As a result, NWFETs have the potential to achieve a higher power density at a temperature limit compared with the FinFETs, especially when the heat removal from the top contact is eased. The impact of the thermal surface resistance of the top contact and substrate thinning on the thermal performance of these two vertical structures is also investigated.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Electrothermal simulation; GaN nanowire field-effect transistor (NWFET); GaN vertical fin field-effect transistor (FinFET); Power transistors; Thermal performance